2022
DOI: 10.7759/cureus.28240
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of Ventral Hernia

Abstract: BackgroundVentral hernias are commonly encountered problems in the field of general surgery. Incisional hernia is a common complication following abdominal surgery that requires reoperation. This study was conducted to understand the incidence of various types of ventral hernia in both sexes and various age groups, predisposing factors, clinical features, and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
3
12
0
4
Order By: Relevance
“…El estudio de Sazhin et al también encontró el IMC, sobrepeso, obesidad y edad como predictores de hernia incisional.9 La frecuencia superior de presentación en el sexo femenino coincidió con estudios previos, así como la historia de cirugía ginecológica previa. 3,4 La hernia incisional es la hernia ventral más común, siendo los factores predisponentes más importantes la obesidad y la constipación según estudios previos. 10 En este estudio el 38% de pacientes presentó obesidad y sólo 1 paciente tuvo antecedente de constipación.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…El estudio de Sazhin et al también encontró el IMC, sobrepeso, obesidad y edad como predictores de hernia incisional.9 La frecuencia superior de presentación en el sexo femenino coincidió con estudios previos, así como la historia de cirugía ginecológica previa. 3,4 La hernia incisional es la hernia ventral más común, siendo los factores predisponentes más importantes la obesidad y la constipación según estudios previos. 10 En este estudio el 38% de pacientes presentó obesidad y sólo 1 paciente tuvo antecedente de constipación.…”
Section: Discussionunclassified
“…3,4 La hernia incisional es la hernia ventral más común, siendo los factores predisponentes más importantes la obesidad y la constipación según estudios previos. 10 En este estudio el 38% de pacientes presentó obesidad y sólo 1 paciente tuvo antecedente de constipación.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…However, a very large percentage of asthma and COPD patients are unable to use their inhalers correctly, and the repercussions are very costly for both patients and healthcare systems [11]. There are studies that have concluded that older people and women are more likely to make mistakes in handling inhaler devices [12][13][14]. The authors of the studies went further and concluded that a higher education level correlates with a lower level of inhaler device handling errors [12,15,16].…”
Section: Introductionmentioning
confidence: 99%